A synthetic agonist at the orphanin FQ/nociceptin receptor ORL1: Anxiolytic profile in the rat - Jenck, François (The National Academy of Sciences, 2000)
The biochemical and behavioral effects of a nonpeptidic, selective, and brain-penetrant agonist at the ORL1 receptor are reported herein. This low molecular weight compound {(1S,3aS)-8- (2,3,3a,4,5,6-hexahydro-1H-phenalen-1-yl)-1-phenyl-1,3,8-triaza- spiro[4.5]decan-4-one} has high affinity for recombinant human ORL1 receptors and has 100-fold selectivity for ORL1 over other members of the opioid receptor family. It is a full agonist at these receptors and elicits dose-dependent anxiolytic-like effects in a set of validated models of distinct types of anxiety states in the rat (i.e., elevated plus-maze, fear-potentiated startle, and operant conflict). When given systemically, the compound has an efficacy and potency comparable to those of a benzodiazepine anxiolytic such as alprazolam or diazepam. However, this compound is differentiated from a classical benzodiazepine anxiolytic by a lack of efficient anti-panic-like activity, absence of anticonvulsant properties, and lack of effects on motor performance and cognitive function at anxiolytic doses (0.3 to 3 mg/kg i.p.). No significant change in intracranial self-stimulation performance and pain reactivity was observed in this dose range. Higher doses of this compound (≥10 mg/kg) induced disruption in rat behavior. These data confirm the notable anxiolytic-like effects observed at low doses with the orphanin FQ/nociceptin neuropeptide given locally into the brain and support a role for orphanin FQ/nociceptin in adaptive behavioral fear responses to stress.